The impact of meme integration on university students’ active learning - Sastre-Hernández, Beatriz María; Chivite-Cebolla, María Peana; Echarte Fernández, Miguel Ángel; Estrella, Álvaro Mendo; Jorge-Vázquez, Javier; Náñez Alonso, Sergio Luis (Institute of Advanced Engineering and Science, 2025)
This study investigates the application of memes as a didactic tool in university-level social sciences education to address the learning needs of generation Z students. In the present study, the problem of the reduction in the academic performance of students is presented to us. With this research we have sought to contrast if the meme tool can help to give an answer to this problem. The methodology was implemented in business administration, economics, and law courses. Students were tasked with designing memes related to course content. A total of 110 memes were submitted by students, and 45 participants completed an evaluation questionnaire. Correlations and a linear regression model were used mainly for data analysis. Regarding the analysis of the results obtained in specific business subjects, where 68 students were evaluated, it should be noted that the meme variable is the second most significant variable in the final grade obtained. This data seems to indicate that, if the students have been able to synthesize part of the contents in memes, this has helped them in a better assimilation of the subject, and to pass it successfully. We certainly know that young people spend a lot of their time on platforms, and the language of memes is familiar to them. These findings suggest that memes can be an effective and engaging educational tool, offering valuable benefits in the digital age for both students and educators.